Economics of Export Restrictions as Applied to Industrial Raw Materials - Fung, K.C.. (OECD Trade Policy Papers, 2013)
Governments intervene in non-renewable natural resources sectors more than in many others, including through the use of export taxes and quotas. Industrial raw materials sectors are characterized by a number of specificities: production is often geographically concentrated, firms are often large with substantial market power, production processes are highly capital intensive, products are relatively homogeneous and potentially substantial differences in costs of production are prevalent. This paper aims to increase understanding of the economic effects of export restrictions, in particular as they apply to the mining sector. It ascertains the prevalence of export restrictions on metals and minerals, proposes a Cournot-Nash model of export restrictions, suggests some of the economic effects due to the presence of export restrictions, and draws some implications for trade policy among producing and consuming countries of non-renewable natural resources